Polymer Nanocomposites : Processing Characterization and Applications - Joseph H.Koo (New York McGraw Hill Education, 2020)
Polymer composites: properties and applications, second edition begins with an overview of key technologies and processes. From there, readers will get in-depth discussions of each topic, including structural, Mechanical, thermal, and Electrical properties as well as commercial and industrial applications. Examples are provided for a wide variety of uses, including coatings for planes and defense vehicles, medical and dental implants, fire-resistant fabrics, and more. This thoroughly revised guide offers a concise introduction to polymer composites that is ideal for Engineers who need to use biomaterials in real-world situations. Written by a recognised expert in the field, The book explains how polymer composites can be used in the aerospace, transportation, construction, energy, health care, textile, and packaging industries. Highlights: 1. Refocused to connect the properties of polymer composites to specific applications in an expanded range of industries and sectors 2. Explains methods and technologies for working with the latest types of commercially available nanomaterials 3. Written by a recognised polymer nanocomposite expert and academic.
Keywords: Engineering and applied operations